PROFILE OF STUDENTS DIFFICULTY IN BIOLOGY LEARNING DURING PANDEMIC COVID-19 IN SMA NEGERI 1 SILANGKITANG - Novita Sari Nasution; Ika Chastanti; Dahrul Aman Harahap (Universitas Negeri Medan, 2021)
The pandemic coronavirus diseases (Covid-19), which has plagued the world, have hampered education implementation, so that the government has issued a policy to implement online learning. This study aimed to determine the difficulties of learning online students in learning biology during the Covid-19 pandemic. This study uses a descriptive method using a qualitative approach. The samples in this study were students and teachers of SMA Negeri 1 Silangkitang, Labuhanbatu Regency. The data analysis technique was carried out in a descriptive qualitative manner using the Miles damn Huberman model. The results showed that learning biology during the covid-19 pandemic at SMA Negeri 1 Silangkitang was based on (1) Prepare Learning Tools (46.60%); (2) Independent (80%); (3) Asking questions (43.30%); (4) Looking for Other Sources (36.60%); (5) Anxious (36.60%); (6) Confidence (40%); (7) Concise the Material (40%) (8) Write Important Concepts (40%); (9) Active (23.30%) and (10) Lazy (40%). Online learning carried out during the Covid-19 pandemic has the advantage of being more flexible in using time because it can be accessed anytime and anywhere. Delivery of information is faster and can reach many students using online media. However, there are also weaknesses in online learning; namely, students are not actively involved because there are students whose areas are not covered by the internet network, and there are also students who cannot afford smartphones.